Evaluation of Findings In Positive D-Dimers Cases of Pulmonary Embolism Using Computed Tomography Pulmonary Angiography - Khumaini, Ayatullah Roohullah; Shakil, Usman; Uzair, Muhammad; Mumtaz, Naila; Hussain, Naveed; Sadiq, Nosheen (Pakistan Armed Forces Medical Journal, 2025)
ABSTRACT Objectives: To evaluate findings of Computed Tomographic Pulmonary Angiography in positive D – Dimers cases of pulmonary embolism. Study Design: Descriptive cross-sectional study. Place and Duration of Study: Department of Radiology, PNS Shifa Hospital Karachi, Pakistan from Mar to Aug 2023. Methodology: One hundred and thirty-nine patients fulfilling our inclusion criteria were recruited in the study. Written consent was taken from all patients. Computed Tomographic Pulmonary Angiography was done for all patients and their findings were recorded. Findings of pleural effusion, pericardial effusion, consolidation, pulmonary thromboembolism and collapse were recorded, and their frequency was noted. Impact of variables such as age and gender on outcome were checked. Results: Mean age of the group was 48.24±10.41 years. Ninety-six (69.1%) of our patients were males while 43(30.9%) were females. Pulmonary thromboembolism was noted in 17(12.2%) patients, consolidation in 12(8.6%), pleural effusion in 10(7.2%), pericardial effusion in 4(2.9%) and collapse was noted in 1(0.7%) patient. Pulmonary thromboembolism and pleural effusions were seen in younger age group while consolidation and pericardial effusion dominated in the older age group, however the findings were not statistically significant (p>0.05). Conclusion: Pulmonary thromboembolism was found to be the most common findings of Computed Tomographic Pulmonary Angiography followed by consolidation and pleural effusion. Age and gender did not have a significant impact on the outcome.